2018
DOI: 10.1016/j.injury.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time to post-operative weightbearing on functional and clinical outcomes in adults with a displaced intra-articular calcaneal fracture; A systematic review and pooled analysis

Abstract: The adverse sequelae which are assumed to be associated with starting partial weightbearing already within six weeks after internal fixation of calcaneal fractures, is not supported by literature data. This systematic review suggests that early weightbearing does not result in impaired outcomes compared with more conservative weightbearing regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
0
5
0
3
Order By: Relevance
“…De Boer et al found that early weight bearing regimens did not negatively affect functional outcome after treatment for displaced intra-articular calcaneal fractures. 64 Previously, Smeeing et al showed that early weight bearing tended to accelerate return to work and daily activities compared with late weight bearing, after internal fixation of ankle fractures. 65 Eliasson et al evaluated tendon elongation, mechanical properties, and functional outcomes during the first 12 months after operative treatment of acute Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…De Boer et al found that early weight bearing regimens did not negatively affect functional outcome after treatment for displaced intra-articular calcaneal fractures. 64 Previously, Smeeing et al showed that early weight bearing tended to accelerate return to work and daily activities compared with late weight bearing, after internal fixation of ankle fractures. 65 Eliasson et al evaluated tendon elongation, mechanical properties, and functional outcomes during the first 12 months after operative treatment of acute Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tian et al and de Boer et al agreed with the statement that there is not any influence between an early weight bearing and the occurence of complications [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 95%
“…More and more studies show that permissive weightbearing reduces time to FWB, return to work, and thus lowers the socioeconomic impact, while negative effects on patients reported quality of life, pain or complication rates are rarely reported [ 30 ]. A recent review states multiple positive effects in early weightbearing while aftercare from operatively treated DIACFs [ 31 ]. Although many studies suggested the benefits of early weightbearing, yet there currently is no prospective literature available that compares operatively treated DIACFs followed by 8 to 12 weeks of restrictive weightbearing with permissive weightbearing, let alone subdivided for different fracture types or approaches.…”
Section: Discussionmentioning
confidence: 99%